EVALUATING THE QUALITY OF ONLINE LICENSING SERVICES IN BARRU REGENCY: A FOCUS ON INFORMATION, SECURITY, AND EASE OF USE - Muliati; Sukmiah (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal